2006
DOI: 10.1160/th05-08-0554
|View full text |Cite
|
Sign up to set email alerts
|

Vascular risk factors in sudden hearing loss

Abstract: Low density lipoprotein (LDL) and fibrinogen apheresis was recently reported to be an effective therapy in sudden hearing loss (SHL). In this study, we investigated whether lipoprotein and/or fibrinogen plasma concentrations, related gene polymorphisms and other cardiovascular risk factors are also risk factors for SHL. Total cholesterol, HDL and LDL cholesterol plasma concentrations, fibrinogen levels, and two functionally relevant fibrinogen polymorphisms were determined in 142 consecutive patients and in 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(144 citation statements)
references
References 49 publications
(61 reference statements)
6
129
3
3
Order By: Relevance
“…It has been believed that bacteria- or virus-induced chronic inflammation could cause microvascular injury, vascular endothelial dysfunction, and atherosclerosis, leading to an increased risk of cochlear ischemia [7, 12, 13]. Furthermore, susceptibility to genetic thrombosis or cardiovascular risk factors would further aggravate the risk of cochlear ischemia [14, 15]. The NLR in peripheral blood has not only been proved to be one of the definitive markers of chronic inflammation in the cardiovascular system, it is also a reliable predictor of functional recovery after vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been believed that bacteria- or virus-induced chronic inflammation could cause microvascular injury, vascular endothelial dysfunction, and atherosclerosis, leading to an increased risk of cochlear ischemia [7, 12, 13]. Furthermore, susceptibility to genetic thrombosis or cardiovascular risk factors would further aggravate the risk of cochlear ischemia [14, 15]. The NLR in peripheral blood has not only been proved to be one of the definitive markers of chronic inflammation in the cardiovascular system, it is also a reliable predictor of functional recovery after vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Kazmierczak H and Doroszeweska G 23 concluded that disturbance of glucose metabolism and hyperinsulinemia may be responsible for inner ear diseases, whereas role of disturbance of lipid metabolism remains vague. Likewise, Claudia Rudack et al 24 found correlation between HDL-CH and LDL-CH and SSNHL. Our study shows higher blood uric acid level in SSNHL group compared to control group.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, ISSNHL could also be the result of an ear microcirculation alteration due to genetic prothrombotic susceptibility or cardiovascular risk factors such as hypertension and diabetes [14,15]. A higher blood viscosity may determine damage in ear microcirculation that can produce hearing loss [16,17].…”
Section: Discussionmentioning
confidence: 99%